(untitled) (Research Nepal Journal of Development Studies, 2021)
A review of history of Baram community is a study of history of Baram Community of Gorkha district of Nepal. It is a brief history of the community. Baram people are indigenous people whose language is called Balkura is closely associated with Tibeto- Burmese linguistic class. To write down the brief history of the community the review has been conducted. It is the collection of different available sources presented in references randomly. The study is also based on the interview of Tokman Baram and Bhairab Baram the old men of the community. In conclusion, Barams are exactly like Jirel, Surel, Thami, the mix of Gurung, Magar, Kirant and Sunuwar. They have huge influence from Hinduism and Bonism. Barams are animists or worshipers of nature.